2019
DOI: 10.3847/1538-4357/ab3d34
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Stellar Populations of Globular Clusters from Homogeneous Ca–CN–CH Photometry. V. as a Surrogate cnJWL Index and NGC 6723

Abstract: We introduce new color indices cn ′ JWL (= Ca CTIO − Ca JWL ) and ch JWL [=(JW L43 − b) − (b − y)], accurate photometric measures of the CN band at λ3883 and the CH G band, respectively, in the study of the multiple populations (MPs) in globular clusters (GCs). Our photometric CN-CH relation for a large number of red-giant branch (RGB) in M5 shows that the evolutions of the CN and CH between the CN-w and CN-s populations are not continuous. Armed with our new color indices, we investigate the MPs of NGC 6723, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…We used the filters provided by the CTIO from 2007 to 2010, and we used our own filters since 2012. As we already noted in our previous study (Lee 2015(Lee , 2019c, the original Ca CTIO was designed to have a filter bandwidth and pivot wavelength very similar to that of the Ca AT defined by Anthony-Twarog et al (1991). Due to aging, the Ca CTIO had been degraded, and its original transmission curve had been significantly altered to the shorter wavelength, resulting in having the passband similar to our JWL39 filter (e.g., see Figure 1 of Lee 2019c).…”
Section: Photometric Indices and Color-magnitude Diagramsmentioning
confidence: 87%
See 1 more Smart Citation
“…We used the filters provided by the CTIO from 2007 to 2010, and we used our own filters since 2012. As we already noted in our previous study (Lee 2015(Lee , 2019c, the original Ca CTIO was designed to have a filter bandwidth and pivot wavelength very similar to that of the Ca AT defined by Anthony-Twarog et al (1991). Due to aging, the Ca CTIO had been degraded, and its original transmission curve had been significantly altered to the shorter wavelength, resulting in having the passband similar to our JWL39 filter (e.g., see Figure 1 of Lee 2019c).…”
Section: Photometric Indices and Color-magnitude Diagramsmentioning
confidence: 87%
“…In our previous studies (Lee 2017(Lee , 2018(Lee , 2019a(Lee , 2019c(Lee , 2020Lee & Sneden 2021), we showed that both the cn JWL and ¢ cn JWL indices are very powerful tools to classify MPs in GCs. As we already mentioned, our cn JWL observations were limited to the central part of the cluster, and we decided to use the ¢ cn JWL to classify MPs in 47 Tuc in our current study.…”
Section: Populational Taggingmentioning
confidence: 96%
“…These estimates ensure that both the populations should be well represented in any CMD. The populations differ in helium abundance by Δ ≈ 0.02 or even 0.01 (VandenBerg et al 2018;Milone et al 2018;Lagioia et al 2018;Lee 2019). Therefore, being well represented in a CMD, the populations are nevertheless segregated in colour or magnitude only in some domains of some CMDs, as discussed in Sect.…”
Section: Properties Of the Clustersmentioning
confidence: 92%
“…Each of the clusters has two populations (Dalessandro et al 2014;Mucciarelli et al 2016;Milone et al 2017;Lee 2019). Both the populations of both the clusters are -enriched with 0.3 <[ /Fe]< 0.4 (Rojas-Arriagada et al 2016;Massari et al 2017;Crestani et al 2019).…”
Section: Properties Of the Clustersmentioning
confidence: 99%
“…MPs are known as a global feature for stellar populations at different evolutionary stages in GCs. Most works focus on MPs among the bright giant stars since they are the most luminous sources in most GCs (e.g., Yong et al 2008;Tang et al 2017;Wang et al 2017;Lee 2019). For GGCs, observations also provide substantial evidence which supports the presence of MPs among less-evolved stars, such as MS stars or subgiant branch (SGB) stars (e.g., Lardo et al 2012).…”
Section: Introductionmentioning
confidence: 99%